Isolation and characterization of Bacteria in the ancient Javanese Pegon manuscript: “Layang Watu Gunung” - Rahmani, Tara Puri Ducha; Ahmad, Nur; Anasom, Anasom; Pertiwi, Salsabiela; Niam, Muhammad Yusrun; Kusuma, Hamdan Hadi; Watson, Lee James (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
This research is one of the efforts and the first step in the preservation of historical ancient manuscripts with an interdisciplinary scientific approach. The Unity of Sciences involved in this research are historical science, archaeology, philology combined with natural sciences such as microbiology and biotechnology approaches. The ancient manuscript whose microorganisms were isolated and observed in this study is an ancient manuscript with Pegon letters titled